Geotechnics and Heritage - Lancellotta, Renato, author.
1 online resource
Keywords: "Conservation of monuments and historic sites is one of the most challenging problems facing modern civilization. It involves various cultural, humanistic, social, technical, economical and administrative factors, intertwining in inextricable patterns. The complexity of the topic is such that guidelines or recommendations for intervention techniques and design approaches are difficult to set. This book assesses the role of historic towers as symbols of community identity and how to best preserve this special cultural heritage from a geotechnical point of view. Well-documented, exemplary case histories are shown that highlight the concepts of preservation, integrity and cultural heritage, that must be the starting point for any activity on monuments and historic sites. Dynamic identification techniques and techniques for long term monitoring of historic towers are also indicated, and examples appropriate intervention measures are eventually reported. The book will be of interest to professionals and academics in the wider fields of civil engineering, architecture and cultural resources management, and particularly to those involved in art history, history of architecture, geotechnical engineering, structural engineering, archaeology, restoration and cultural heritage management."--Provided by publisher.